Improvement of Pitting Corrosion Resistance in Type 201 Stainless Steel by Electrochemical Method in Nitric Acid Solution - Sri Hastuty; Fayza Yulia; Nonni Soraya Sambudi; Alfian Kahfi Fauzi; Fatwa Khoirrun Nadhor (Jurnal Kimia Sains dan Aplikasi, 2025)
Stainless steel is widely utilized across industries due to its robust resistance to corrosion. Stainless Steel 201 (SS201), characterized by a lower nickel content compared to grade 304, is valued for its cost-effectiveness and strong mechanical properties. However, SS201 is more prone to pitting corrosion in aggressive environments than SS304. This research aims to enhance SS201’s resistance to pitting corrosion through surface treatment involving nitric acid. Cyclic voltammetry was conducted using nitric acid concentrations of 1, 2, and 3 M. The findings indicate that higher concentrations of nitric acid improved corrosion resistance, with 3 M resulting in a pitting depth of 23.667 μm. The application of citric acid contributed to enhanced resistance against pitting corrosion by fostering a chromium-rich surface.